1992
DOI: 10.1111/j.1475-4991.1992.tb00452.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Income and Wealth in Japan

Abstract: This paper reviews research on the distribution of income and wealth in Japan, identifies sources of data on income and wealth, and describes limitations of these data. Evidence that Japan's poorest income groups are relatively well‐off is convincing, but there is less evidence that the overall distribution of income in Japan is more equal than in other OECD countries. Agricultural policy, social welfare policy, the tax system, trends in earnings differentials, and the role of the Japanese family are among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In France, the incom es of male heads of household becam e m uch m ore unequal although the sam e did not hold for fam ily incom es. Bauer & M ason (1992), however, find no increase in incom e inequality in Japan nor in Sweden. Utilising an indicator of poverty based on the post-tax, post-transfer distribution of fam ily incom e, recent O ECD estim ates for a sam ple of ten countries show that poverty increased during the 1980s and 1990s in the US, West G erm any, Italy and the N etherlands, while this indicator of poverty declined in F rance and Canada (see O ECD, 1997a).…”
Section: Trends In G Rowth and Distribution: A Com Parative Perspectivementioning
confidence: 73%
“…In France, the incom es of male heads of household becam e m uch m ore unequal although the sam e did not hold for fam ily incom es. Bauer & M ason (1992), however, find no increase in incom e inequality in Japan nor in Sweden. Utilising an indicator of poverty based on the post-tax, post-transfer distribution of fam ily incom e, recent O ECD estim ates for a sam ple of ten countries show that poverty increased during the 1980s and 1990s in the US, West G erm any, Italy and the N etherlands, while this indicator of poverty declined in F rance and Canada (see O ECD, 1997a).…”
Section: Trends In G Rowth and Distribution: A Com Parative Perspectivementioning
confidence: 73%
“…There have long been debates on the most suitable data sets for the analysis of income inequality in Japan, and it can be argued that there is a need for a thorough review. It should be noted, however, that the claim regarding the exclusion of households primarily engaged in agriculture in the NFIES made by Bauer and Mason (1992) and cited by Mira D'Ercole is not correct. Also, of relevance is the work of Mira d'Ercole (2006) comparing income inequality in Japan to other OECD countries using the CSLC, and pointing to the work of Bauer and Mason (1992) and suggesting that the 'data from the National Survey of Family Income and Expenditure were less suitable for cross-county comparisons than those provided by the Comprehensive Survey, because of the exclusion of households primarily engaged in agriculture and of significant under-reporting of social security and property income' (Mira d'Ercole, 2006: 12).…”
Section: Methodsmentioning
confidence: 99%
“…For example, when discussing the controversy around income inequality statistics for Japan, Chiavacci (2008) highlighted that organisations such as the World Bank use the NSFIE, whereas other studies (including the more recent work of the OECD and that of Tachibanaki, 1998) are based on the CLCS. Also, of relevance is the work of Mira d'Ercole (2006) comparing income inequality in Japan to other OECD countries using the CSLC, and pointing to the work of Bauer and Mason (1992) and suggesting that the 'data from the National Survey of Family Income and Expenditure were less suitable for cross-county comparisons than those provided by the Comprehensive Survey, because of the exclusion of households primarily engaged in agriculture and of significant under-reporting of social security and property income' (Mira d'Ercole, 2006: 12). The last comprehensive attempt to provide such a review was twenty years ago by Bauer and Mason (1992), who identified and reviewed suitable income and wealth data in Japan and highlighted the substantial variation in income inequality measures between studies based on different Japanese data sets, arguing that 'given these data problems, the country's relative ranking in international comparisons of income equality is a matter of some dispute' (Bauer and Mason, 1992: 426).…”
Section: Methodsmentioning
confidence: 99%
“…Other factors have also been observed to affect income inequality. For instance, Bulir (2001) observes that price stability, among other factors, would improve income inequality in a given country, while Whalley and Zhang (2007) find that removing migration restrictions in China would improve income inequity, and Bauer and Mason (1992) find that, in the case of Japan, the rapid appreciation of the stock market and land prices during the late 1980s led to greater inequality in the distribution of wealth.…”
Section: A Selective Review Of Studies On Income Inequalitymentioning
confidence: 99%